Effect of local and systemic administration of atorvastatin for improving bone healing on critical defects - de Miranda-Filho, Fábio Vieira [UNESP]; Barbosa, Stéfany [UNESP]; Panigali, Olavo Alcalde [UNESP]; Silva, Mirela Caroline [UNESP]; da Costa, Monique Gonçalves [UNESP]; Flores, Franciele da Silva [UNESP]; Ervolino, Edilson [UNESP]; Theodoro, Letícia Helena [UNESP]; Magro-Filho, Osvaldo [UNESP]; Faverani, Leonardo Perez [UNESP] (FapUNIFESP (SciELO), 2024)
This study aimed to evaluate the impact of atorvastatin, administered both locally and systemically, on critical defects in the calvaria of rats. Thirty-six adult rats were randomly assigned to three groups, with all bone defects covered by a collagen membrane. The groups received different treatments: distilled water (GAD), where membranes were soaked in distilled water; systemic application of atorvastatin (GAS) at a dosage of 3.6mg/kg/day through gavage; and local application of atorvastatin (GAL). After 14 and 28 days, all animals were euthanized, and various assessments were conducted, including histometric analysis, measurement of linear residual defect, evaluation of newly formed bone area, determination of membrane and soft tissue area, cell count, and immunohistochemical analysis. Group GAS exhibited a significant reduction in residual defect compared to the other groups (p<0.05) and a lower number of osteocytes (p<0.05) in comparison with other groups. On day 28, both GAL and GAS groups showed a higher number of inflammatory cells compared to GAD (p<0.05). Immunolabeling of CD31 was similar for both groups, but in the case of osteocalcin, there was a significant increase in labeling for groups GAS and GAL between days 14 and 28 postoperative (p<0.05). In conclusion, systemic atorvastatin demonstrated enhanced osteogenesis in critical calvaria defects in rats, suggesting its efficacy in promoting bone regeneration without exerting a notable anti-inflammatory effect.
Keywords: atorvastatin; bone regeneration; Osteogenesis